A study on employee's perception towards women leadership effectiveness at Selangor Treasury / Izzati Syafiqah Mohammad Hisham and Nurul Nadia Mohd Zamani - Mohammad Hisham, Izzati Syafiqah; Mohd Zamani, Nurul Nadia (2016)
This research will be review on the employee's perception towards women leadership effectiveness in Selangor Treasury. In this study, there were 132 of civil servant in the Selangor Treasury involved as the respondent. This research conducted the study based on four selected leader behaviours include communication skills, usage of power, decision-making skills, and personal characteristics and also demographic factors. The result shows that there is no difference between the demographic factors (gender, age, educational level and length of service) in perceiving women leadership effectiveness based on four leader's behavioural aspects (communication skills, usage of power, decision-making skills, personal characteristics).